Latin American perceptions of fear and exaggeration transmitted by the media with regard to COVID-19: frequency and association with severe mental pathologies - Mejia, Christian R. (2023)
Introduction: The COVID-19 pandemic contributed to the spread of abundant misinformation by the media, which caused fear and concern. Objective: To determine the association between the pathologies of the mental sphere and the perceptions of fear and exaggeration transmitted by the media with respect to COVID-19 in Latin America. Methodology: The present study has an analytical cross-sectional design that is based on a validated survey to measure fear and exaggeration transmitted by the media and other sources (Cronbach’s α: 0.90). We surveyed more than 6,000 people, originally from 12 Latin American countries, who associated this perceived exaggeration with stress, depression, and anxiety (measured through DASS-21, Cronbach’s α: 0.96). Results: Social networks (40%) or television (34%) were perceived as the sources that exaggerate the magnitude of the events. In addition, television (35%) and social networks (28%) were perceived as the sources that generate much fear. On the contrary, physicians and health personnel are the sources that exaggerated less (10%) or provoked less fear (14%). Through a multivariate model, we found a higher level of global perception that was associated with whether the participant was older (p = 0.002), had severe or more serious anxiety (p = 0.033), or had stress (p = 0,037). However, in comparison with Peru (the most aected country), there was a lower level of perception in Chile (p < 0.001), Paraguay (p = 0.001), Mexico (p < 0.001), Ecuador (p = 0.001), and Costa Rica (p = 0.042). All of them were adjusted for gender and for those having severe or major depression. Frontiers in Psychology 01 frontiersin.or Mejia et al. 10.3389/fpsyg.2023.1037450 Conclusion: There exists an association between some mental pathologies and the perception that the media does not provide moderate information.